Shape recovery studies for coupled deformations in an epoxy based amorphous shape memory polymers. (December 2015) - Sujithra, R.; Srinivasan, S.M.; Arockiarajan, A.
Abstract: In this work, the effect of sequence of shape setting on the shape recovery response for an epoxy based amorphous SMP was studied. The shape setting for coupled axial-twist deformations was done at two different temperatures within the glass transition band. A simple set-up with cameras was used to study the shape recovery behavior under free recovery experiments. Results show that the recovery behavior is independent of sequence of shape setting process but a shift in the shape recovery curve is noticed. The shape memory cycle for coupled deformations was also simulated in ABAQUS-VUMAT using the model proposed earlier by the authors based on multiple natural configurations. The simulated results show the capability of the model to analyze the memory effects of an amorphous polymer subjected to coupled deformations.